(untitled) (Fiep Bulletin - online, 2015)
This study is characterized as being of speculation and the one case, having as purpose to identify to the magnitude of impact during the execution of the bandal thagui kick of Taekwondo. The citizen of the research was an individual of the sex masculine with 24 years, corporal mass 80 kilograms, stature of 1,80m, black belt 2° Dan, 11 years practising Taekwondo and competing 10 years in the modality. For measurement of the impact magnitude was used one triaxial accelerometer connected to a system of data acquisition. Four series of 10 lateral kicks had been carried through to average height against the target, with a frequency of acquisition of 5.000 Hz, and total time of acquisition of 5 seconds with interval of 30 minutes between the series to rest of the athlete. The impact results had presented in average the values for x=71,81g±15,30g, y=334,88g±64,66g and z=166,98±18,80g in the foot at the moment of the kick. The times had presented in x=0,11s±0,02s, y=0,02s±0,01s and z=0,02s±0,01s. Thus, it concludes that in function of the great amount of repetition and the high values of impact in the kicks, the structure of the foot becomes more susceptible the injuries.